2018
DOI: 10.1017/jgc.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

The Centrality of Connectedness: A Conceptual Synthesis of Attending, Belonging, Engaging and Flowing

Abstract: Over the past decade, researchers have called for a reconceptualisation of school connectedness. A review of literature between 1990 and 2016 was completed to define school connectedness and identified four factors: attending, belonging, engaging, and flow. The review of the published literature from 1990 to 2016 that related to the four factors was undertaken to define each of these terms and their relevance to school connectedness.Subsequently, based on the four factors, a sequential, four-level model of sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 68 publications
(98 reference statements)
2
21
0
Order By: Relevance
“…A sense of belonging is a fundamental and pervasive human need that is based on strong biological and psychological mechanisms [ 21 ]. Extensive evidence emphasizes the importance of feeling connected to others and social institutions for adolescent mental health and well-being [ 12 , 18 , 22 ]. The centrality of connectedness is embedded in various theories and models (e.g., attachment theory [ 23 ], family warmth and cohesion [ 24 ]) that support healthy connections as a fundamental need between youth and their families.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A sense of belonging is a fundamental and pervasive human need that is based on strong biological and psychological mechanisms [ 21 ]. Extensive evidence emphasizes the importance of feeling connected to others and social institutions for adolescent mental health and well-being [ 12 , 18 , 22 ]. The centrality of connectedness is embedded in various theories and models (e.g., attachment theory [ 23 ], family warmth and cohesion [ 24 ]) that support healthy connections as a fundamental need between youth and their families.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, research on social support, integration, and connection highlights the advantages of forming positive relationships outside of the immediate family [ 11 , 12 , 25 ]. As a growing framework for intervention, connectedness is a malleable mechanism that contributes to an improved sense of belonging, increase in social networking, and potential engagement in one’s social environment [ 22 ]. Not only is social connectedness instrumental in optimal outcomes for youth, but a lack of such connections have been linked to poor mental and physical health among youth [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…School belonging -the belief held by students that adults and peers in the school care about their academic progress as well as about them as individuals -is another important protective factor (Kraft and Dougherty, 2013). A review of research has shown that young people who feel connected to their school are less likely to engage in many risk behaviours (Bowles and Scull, 2019). Positive peer group interactions more generally can also act as a buffer to behavioural problems (Gray et al, 2018).…”
Section: Introduction |15mentioning
confidence: 99%
“…These interactions can lead to positive peer relationships, friendship building, learning problem solving skills during play and peer acceptance (Stanton-Chapman, 2015). These qualities, along with having a sense of school belonging are considered paramount for a child's social development as they have been found to be associated with reduced substance related issues, violence and gang involvement (Bowles and Scull, 2018). Furthermore, a study by Perdue et al (2009) showed that peers played an important role for school engagement where it was found that having supportive peer friendships was a strong predictor for school retention.…”
Section: Introductionmentioning
confidence: 99%